The "three branch model" of Further Education of in-company Vocational Educators : Linking in-company Learning Projects, external training in Further Education and University Learning - Schrode, Nicolas [Verfasser] (My University, 2017)
"This article describes a new model of qualification of in-company vocational educators which was constructed by linking three different existing qualification paths in Germany: in-company learning, external training in Further Education and University learning. It is called Triales Modell (three branch model of Further Education). Before outlining the model, this paper first introduces some facts about the group of in-company vocational educators and points out their main previous and existing training opportunities in Further Education. It especially mentions two new opportunities: The Gepr. Aus- und Weiterbildungspädagoge (Professional of Human Resource Services Management) and the Gepr. Berufspädagoge (Professional of Vocational Training) which are trainings that take up specific pedagogical needs. On the basis of research findings, the paper proposes the thesis that in addition to that there is still a need of more and other skills than these two qualifications could offer: Scientific competences that can be acquired at universities. Referring on that backgrounds, the author describes the new model. In linking the mentioned qualification paths the Triale Modell makes it possible to integrate the strengths of the different places of learning like practical relevance and theoretical foundation. Its construction shortens learning times, avoids having to learn the same things twice and creates new possibilities of permeability between vocational and academic education. For vocational educators it offers a chance for professionalization." (author's abstract; BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; S 1.4 Hochschulbildung; Bildungspersonal; Triale berufspädagogische Weiterbildung; Geprüfter Berufspädagoge; Geprüfter Aus- und Weiterbildungspädagoge